Konsep Didikan Menurut Mazmur 128 - Sihar Daniel Manurung (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2025)
The fragile mental resilience of today’s youth—often called the strawberry generation—motivates this study. While outwardly creative and appealing, many young people lack strength to face life’s pressures and challenges. This contrasts sharply with the image of children as olive shoots in Psalm 128, representing strength, endurance, and fruitfulness. This research examines how family-based education rooted in Biblical principles can cultivate a resilient, steadfast generation. Using a qualitative literature review and hermeneutic analysis, the study concludes that nurturing faith in God, modeling responsibility and integrity, and sustaining consistent, personal education are key in raising a generation strong like olive trees, able to endure life’s trials and remain productive and faithful.